O politicamente correto e a Constituição de 1988: liberdade de expressão e minorias - Jatene, Karina Kassis dos Reis (2016)
The theme to be developed is related to the fundamental right to freedom of expression against the right to non-discrimination of minorities, from the perspective of "political correctness". It is intended to highlight the restrictions on freedom of expression resulting from it, minority protection movement. From another angle, freedom of expression does not allow hate speech or incitement to violence. The promotion of tolerance in a multicultural society is the scenario that is aimed. Freedom as an institute, from which stems the freedom of expression in all its aspects (freedom of expression of thought, freedom of conscience, belief and religious worship, freedom of communication and information) as well as the restrictions imposed on this fundamental right, will be analyzed in the first chapter. The second chapter is dedicated to the minority race and ethnicity; woman; people with disability and sexual orientation. The reasons that characterize these groups as minority and vulnerable, as well as the scope of national and international protection will be expounded. The "political correctness" is the theme of the third chapter. It is a protective movement of minorities that develops primarily in the behavioral quadrant and freedom of expression. In the fourth chapter multiculturalism is studied, an outstanding feature of contemporary Western society. The diversity and coexistence - voluntary or involuntary - of different social groups is the main reason to intolerance. The fifth and final chapter is devoted to the highlight of the right of opinion and dissent, and its essential nature to democracy. It is also developed an explanation about the principle of proportionality as a method to weigh the fundamental rights at stake, to illuminate the tortuous path in the search for coexistence of divergences